Raj Guruju of Śrīkhaṇḍa Tarumūla Mahāvihāra: His Role in Buddhist Community of Kathmandu - Bajracharya, Aakasha (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: Sikhamu Baha, Śrīkhaṇḍa Tarumūla Mahāvihāra, is one of the prominent Buddhist monasteries of Kantipur with a history backed around 7th century CE. It is situated in a small, enclosed courtyard adjoining the Kumari Baha and just off of the Durbar Square. The importance of this baha is the fact that one of its members is the ’Raj Guru’, or Raj Gubhaju. This post is hereditary and is always held by a Vajrācārya of one of the lineages of Sikhamu Baha. Objective: The objective of this article are to understand the different activities performed by Rajguru in the past and present, to highlight the facts regarding Raj Guruju, its history as well as his role in the buddhist community of Kathmandu and to showcase the linkage between Kumari and Raj Guruju. Methodology: The study follows descriptive research methodology and interviews are conducted to meet the research objective. Result: The findings of this study is that the Raj Guruju has been playing an eminent role in creating a balance in Buddhist community, working for benefit of Vajrācārya s of Kathmandu, fulfilling his duty as royal priest and also addressing the contemporary issues arose along with time. Conclusion: Raj Guruju is a hereditary post held by Vajrācārya of “Yuta kaval” of Śrīkhaṇḍa Tarumūla Mahāvihāra. Raj Guruju being still a prominent and influential post amongst the Bajracharya of Kathmandu. He is the guardian of Bajracharyas in Kathmandu. He plays an eminent role in creating a balance in Buddhist community, working for benefit of Bajracharyas of Kathmandu. Along with the role towards Bajracharya community as a whole, Raj Guruju has special linkage with Kumari and Kumari chhen and thus has to follow his duties and specific roles in Kumari Chhen as well.